Collective behaviour in basketball: a systematic review - Courel-Ibanez, J.; McRobert, A. P.; Ortega Toro, E.; Cárdenas Vélez, D. (International Journal of Performance Analysis in Sport, 2017)
We aimed to review and organise current literature about basketball collective behaviour assessment to categorise the most common research topics, main findings and shortcomings of the analysis made. Literature was sought via an electronic search of three databases: Scopus, Web of Science and SportDiscus. Systematic review principles were used to identify and select potential eligible studies according to defined inclusion and exclusion criteria. In total, 322 studies were identified in the original database search, including 45 after the screening process. Then, articles were classified regarding topic and tactical factors explored (game context, game phase and players` role, and game condition). Current findings contribute to a better understanding of tactical assessment and game structure in basketball. The set of results extracted and discussed provide accurate information about the state of art in basketball collective behaviour assessment. We detected a lack of studies exploring tactical behaviour from a complex, dynamic, and holistic point of view, as well as an absence of longitudinal designs. Besides, reports about the influences of game context in basketball tactical performance are sparse. Information reported might result of great interest for coaches and staff, contributing to better characterise match performance in basketball and subsequent development of tactical training enhancement programmes. Additionally, the summary and classification provided may serve as a useful guide to future research in basketball.